2015
DOI: 10.1093/protein/gzv048
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of a system for the co-translational incorporation of a keto amino acid and its application to a tumour-specific Anticalin

Abstract: The bioorthogonal keto group has attracted interest for the site-specific chemical conjugation of recombinant proteins under mild conditions, e.g. with aminooxy-functionalised fluorescent probes, radiometal chelates, toxins or polymers. However, the cotranslational incorporation of the corresponding non-canonical amino acid p-acetyl-L-phenylalanine (Apa) into proteins expressed in Escherichia coli by means of amber suppression using a previously described system with a mutated tRNA and an engineered tyrosyl-tR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…70 Later, a ketone group was introduced into ANTICALIN s N7A for conjugation with Alexa 488, which realized safe ED-B detection at the cellular level and demonstrated its potential as an in vivo imaging probe. 71 Meanwhile, prostate-specific membrane antigen (PSMA) and vascular endothelial growth factor receptor-3 (VEGFR-3)-specific anticalins combined with immunofluorescence staining were shown to exhibit high binding affinity and selectivity to PSMA-and VEGFR-3-positive cells, demonstrating the potential of these anticalins for further in vivo imaging and therapy studies of solid tumor. 72,73 The 70 kDa heat-shocking protein (HSP70) is commonly expressed in primary and metastatic tumors and is commonly upregulated after radiochemotherapy treatment.…”
Section: Affibodymentioning
confidence: 99%
“…70 Later, a ketone group was introduced into ANTICALIN s N7A for conjugation with Alexa 488, which realized safe ED-B detection at the cellular level and demonstrated its potential as an in vivo imaging probe. 71 Meanwhile, prostate-specific membrane antigen (PSMA) and vascular endothelial growth factor receptor-3 (VEGFR-3)-specific anticalins combined with immunofluorescence staining were shown to exhibit high binding affinity and selectivity to PSMA-and VEGFR-3-positive cells, demonstrating the potential of these anticalins for further in vivo imaging and therapy studies of solid tumor. 72,73 The 70 kDa heat-shocking protein (HSP70) is commonly expressed in primary and metastatic tumors and is commonly upregulated after radiochemotherapy treatment.…”
Section: Affibodymentioning
confidence: 99%
“…After several rounds of DNA shuffling and selection, a quadruplet mutant ncAARS was identified that along with mutRNA efficiently assigned the stop codon to the ncAA. Since the initial report of this Tyr analog OTS­(CUA), a variety of modifications to the selection strategy have been published, including suppression of amber stop codons in the T7 RNAP gene with a reporter gene under control of the T7 promoter, or in a reporter gene itself, such as GFP, with mutant isolation via FACS. , With these approaches Tyr analog OTS­(CUA) variants that direct the incorporation of other ncAAs have been developed by altering the specificity of the ncAARS, and those that direct the incorporation of ncAAs that enable subsequent bioorthogonal reaction, such as p -acetyl- l -phenylalanine (AcF) or p -azido- l -phenylalanine (AzF) (Figure ), are of special interest for this perspective. These studies have also elucidated key amino acid residues that mediate ncAA specificity.…”
Section: Gce Via Codon Reassignmentmentioning
confidence: 99%
“…However, the most common limitation of the first generation ncAARSs is typically their significantly reduced activity . Activity has been increased in some cases through random mutations, , but most efforts have focused on introducing mutations that are expected to mediate direct interactions with the ncAA or tRNA CUA . , For example, Amiram et al chromosomally integrated two previously evolved Tyr analog OTS­(CUA) variants (for AcF or AzF), diversified the ncAARSs at the amino acid or anticodon binding sites, and used a novel tolC/ colicin-based negative selection and GFP-based FACS positive selection to identify variants that were up to ∼25-fold more efficient in the production of GFP with three instances of the ncAA . Another study comparing selection conditions suggested that, while less stringent conditions may result in ncAARSs that produce more protein in the absence of the ncAA, the selected ncAARSs can still have sufficient ncAA recognition to outcompete mis-suppression in their presence …”
Section: Gce Via Codon Reassignmentmentioning
confidence: 99%
“…Nevertheless, supplementation-based incorporation (SPI) only allows for the insertion of isosteric analogues of cAAs, the structural diversity of which is restricted by the promiscuity of the respective tRNA and aminoacyl-tRNA synthetase and limited by the use of auxotrophic strains 13 14 15 . Expanding the structural complexity of the ncAA regardless of the amino acid to be replaced, can be achieved by stop-codon-suppression (SCS) or reassignment of a sense codon but requires the design of new pairs of orthogonal tRNA and the corresponding aminoacyl-tRNA synthetases 8 16 17 18 19 20 21 22 and genetic modifications such as introduction of the respective codon in the addressed gene and removing of suppressor tRNAs or release factor 1 for improved yields 23 24 25 26 . Herein we report the use of fully adapted E. coli MT21 as a platform for production of ncAAs-containing small-molecule-type antibiotic peptides, which undergo massive post-translational modifications, being only recently addressed in the frame of single protein/peptide recombinant production by using standard expression strains 1 10 11 .…”
mentioning
confidence: 99%